Detection Determinants of Bank Sustainability Report - Aprilia, Fadilla; Kustinah, Siti (Jurnal Akuntansi, 2024)
Abstract Purpose - This study aims to determine the effect of board gender diversity, narcissism, and audit committee meeting intensity on sustainability reports in the banking company sub-sector listed on the Indonesia Stock Exchange (IDX) for 2018-2022. Design/methodology/approach - This study is a quantitative study that uses secondary data, namely data that has been processed in finished form and has been published. The population in this study are banking company sub-sector listed on the Indonesia Stock Exchange (IDX) for 2018-2022. The sample in this study was 12 companies with five years of observation using purposive sampling techniques to obtain 60 samples. The data analysis techniques used in this study are classical assumption test analysis, multiple linear regression test, correlation test, determination test, and t-test using SPSS 27 software. Findings - The results showed board gender diversity has a negative effect on sustainability reports, narcissism does not affect sustainability report, and audit committee meeting intensity has a positive effect on sustainability reports.Research limitations/implications - This research also provides a basis for further research into the relationship between organizational factors, leadership, and sustainability. Keywords: Board Gender Diversity, Narcissism, Audit Committee, and Sustainability Report Disclosure